Pemanfaatan Metode Clustering untuk melihat pola penjualan dan perilaku pembelian konsumen, pada penjualan tiket pesawat PT. Garuda Indonesia, Cabang Batam - Rivort Pormes; Daniel H. F. Manongga (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Analysis of data mining on data sales aims to process data with limited attributes to know information that can be generated from processing of such data. The utilization of Clustering Method are expected to answer the needs of processing the data to figure out the pattern of most purchases and distance of purchases up to the day of departure at the data in two years on PT Garuda Indonesia, Batam Branch. Data Mining Processing aims to process sales data into information or knowledge which plays an important role as one of the solutions in determining the future strategy. The use of the K-means algorithm aims to see algorithm processing capabilities with limited attributes. The purpose of using this method is to obtain the largest purchasing frequency information each month as well as consumer purchasing patterns as reference in establishing business recommendations as well as acquiring knowledge which will be useful for PT Garuda Indonesia, Batam Branch. By considering the existence of business competition of other airline companies, the result is expected to bring feedback as material input for the company in the future.